(3GdeSCdI GdScGfjI hbVjI JfXje GdCSQI aj GdHdOGf GdYQHjIs (3OQGSI aj GdefgLs - (3GHQGgje(B, (3YHO Gddgs ((3HjQhJs (3GdeQcR GdKbGaj GdYQHjs, 1994)
(3efWb GdHMK aj QDjI GdGehQ hbVGjG efgLjI(B- (3GdeSCdI GdScGfjI hbVjI JfXje GdGSQI(B- (3EYGOI GfJGL GdeSCdI GdScGfjI hJfXje GdGSQI aj GdHdOGf GdYQHjI(B.s
Keywords: (3GdCSQIs; (3GdScGfs; (3JfXje GdCSQIs